What drives the inflow of FDI in OIC countries? Evidence from Top 10 hosts of inward FDI flows - Indri Supriani; Bayu Arie Fianto (Faculty of Economics, Universitas Islam Indonesia, 2020)
Purpose – This study investigates the driven factors of Foreign Direct Investment (FDI) inflow in selected OIC member countries. The selection of samples observation based on the top 10 hosts of inward FDI flows countries, includes the United Arab Emirates (UAE), Morocco, Indonesia, Turkey, Iran, Egypt, Bangladesh, Kazakhstan, Oman, and Malaysia.Methodology – The data for this study are obtained from World Bank and United Nations Development Programme (UNDP) database for the period 2001-2018. This study adopted panel regression analyses and utilized the Random Effect Model.Findings – This study reveals that GDP and trade openness were positive and significantly plays a vital role in driving the FDI inflow. Whereas, the exchange rate, inflation, and human development index did not have a significant impact on FDI inflow in the top 10 hosts of inward FDI flows countries.Research limitation – The main limitation of this research is the lack of a variable that represents the Islamicity index, which can differentiate the driven factors of FDI in Muslim and non-Muslim organization countries.Practical implication – This study suggests that members of OIC countries should provide a conducive investment environment which is represented by higher GDP growth and engage in various international trade agreements because those factors have higher possibilities in impacting the FDI inflow. Moreover, the rules which describe the investment priority amongst the member of OIC countries must be ratified immediately to decrease the percentage of the FDI inflows goes to non-OIC members.Originality – This study has advanced the knowledge by examining the driven factors of FDI in the specifically selected members of OIC countries, which based on the highest FDI inward. Thus, this study provides significant insights for policymakers for the rest of the member OIC countries to attract FDI inflows referring to the top 10 hosts of inward FDI flows countries.